A Critical Review on Avipathi Choorna- A Unique Formulation for Peptic Ulcer Disease - Subha K Nampoothiri,; A Shahul Hameed, (International Journal of Ayurveda and Pharma Research, 2021)
Peptic-ulcer-disease is the ulceration of gasrtric or duodenal mucosa due to the digestive action of pepsin and stomach acid. Gastritis, gastric ulcer and duodenal ulcer are included under this. It can be correlated with the condition Parinamasoola mentioned in Ayurveda. Avipathichoornam is a famous Ayurvedic formulation, mentioned in the texts Ashtanga Hridaya and Sahasrayoga. Avipathi choorna exerts its effect in Peptic ulcer disease probably through Deepana, Pachana and Saraka actions by virtue of the pharmacological properties of the ingredients with which the vitiated Pitta can get normalized. It can be deducted that Avipathi choorna probably neutralize the excess acid secretion in the gastrointestinal tract and maintain a healthy pH. The formulation also probably acts by the anti inflammatory property of most of the ingredients which can help pacify the inflamed tissue layer of the gut. The aim of this paper is to demonstrate mode of action of Avipathi choorna in peptic ulcer disease by critically analyzing the pharmacological properties as well as chemical constituent of the ingredients.